Feeling and Time: The Phenomenology of Mood Disorders, Depressive Realism, and Existential Psychotherapy - Ghaemi, S. Nassir (Oxford University Press, 2007)
Phenomenological research suggests that pure manic and depressive states are less common than mixtures of the two and that the two poles of mood are characterized by opposite ways of experiencing time. In mania, the subjective experience of time is sped up and in depression it is slowed down, perhaps reflecting differences in circadian pathophysiology. The two classic mood states are also quite different in their effect on subjective awareness: manic patients lack insight into their excitation, while depressed patients are quite insightful into their unhappiness. Consequently, insight plays a major role in overdiagnosis of unipolar depression and misdiagnosis of bipolar disorder. The phenomenology of depression also is relevant to types of psychotherapies used to treat it. The depressive realism (DR) model, in contrast to the cognitive distortion model, appears to better apply to many persons with mild to moderate depressive syndromes. I suggest that existential psychotherapy is the necessary corollary of the DR model in those cases. Further, some depressive morbidities may in fact prove, after phenomenological study, to involve other mental states instead of depression. The chronic subsyndromal depression that is often the long-term consequence of treated bipolar disorder may in fact represent existential despair, rather than depression proper, again suggesting intervention with existential psychotherapeutic methods.